Plasmid-encoded trimethoprim resistance in multiresistant epidemic Salmonella typhimurium phage types 204 and 193 in Britain. Issue 6225 (17th May 1980) - Threlfall, E J; Ward, L R; Ashley, A S; Rowe, B
Abstract : Multiresistant strains of Salmonella typhimurium phage types 204 and 193 appeared in calves in 1977 and then spread epidemically in cattle. Food poisoning is the main route by which drug-resistant strains from cattle are spread to man, and by the end of 1979 these two multiresistant strains had been identified in 290 cases of human salmonellosis in Britain. Trimethoprim-resistant S typhimurium were rare until a strain of a new phage type, designated type 204c, spread in cattle in 1979. All isolations of type 204c were trimethoprim resistant. Trimethoprim had been used to treat cattle and this usage has probably contributed to the establishment of type 204c and the increased incidence of trimethoprim-resistant strains. The responsibility to prevent or control drug resistance in bovine S typhimurium lies with the veterinary profession, and more stringent regulatiions governing the use of antibiotics in animals bred for food may be necessary.